PENGEMBANGAN MEDIA KARTU KUARTET BERBASIS LOCAL WISDOM UNTUK MENINGKATKAN PEMAHAMAN KONSEP DALAM PEMBELAJARAN IPAS KELAS IV MI - Hana, Rissiril; Nurhaningtyas Agustin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop a local wisdom-based quartet card learning media to improve students’ conceptual understanding in IPAS learning at the fourth-grade level of Islamic elementary school. The background of this study is the low conceptual understanding of students caused by conventional learning methods and the lack of innovative learning media. This research used a Research and Development (R&D) approach with the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The subjects of this study were 14 fourth-grade students. The instruments used included validation sheets, observation sheets, and response questionnaires, as well as pretest and posttest. Data were analyzed using percentage techniques and N-Gain. The results showed that the developed media achieved a validity level of 92% (very valid) after revision, a practicality level of 100% (very practical), and an effectiveness level indicated by an N-Gain score of 0.58 (moderate category). In addition, student and teacher responses were very positive, reaching 100% and 91%, respectively. These findings indicate that the local wisdom-based quartet card media is valid, practical, and effective in improving students’ conceptual understanding. Therefore, this media can be used as an alternative learning tool to create more engaging and meaningful learning experiences.